Cortical Areas Involved in Subjective Visual Vertical Perception: A Systematic Review - Meymaneh Jafari; Hojjat Allah Haghgoo; Seyed Ruhollah Hosseini; Hassan Ashayeri; Enayatollah Bakhshi; Moslem Shaabani (Auditory and Vestibular Research)
Background and Aim: The information related to brain oscillation, head rotation and head orientation relative to gravity is obtained from the vestibular system. An important reference for upright posture and navigation is gravity-based vertical perception. Many studies have been conducted for the determination of cortical areas involved in Subjective Visual Vertical (SVV) perception in healthy people or patients with brain injuries. Their results have indicated an extensive and bilateral cortical area involved in SVV perception. The purpose of this review study is to investigate these cortical areas and their functional role. Recent Findings: Neuroimaging studies in patients with brain injuries showed that multiple cortical areas have a role in SVV perception. These areas mainly include the occipital cortex, frontal cortex, posterior temporoparietal, temporo-occipital, parieto-occipital, superior temporal gyrus, inferior parietal lobe in temporoparietal junction, posterior insula, cuneus, lingual gyrus, precuneus, ventral dentate nucleus, cerebellum, and brainstem. Conclusion: The cortical areas involved in SVV perception are a part of the vestibular system, which is distributed bilaterally. These areas have a multi-sensory processing task and play a role in processing of cognitive and motor sensory information.